Pulse-wave velocity assessments derived from a simple photoplethysmography device: Agreement with a referent device - Zieff, Gabriel; Stone, Keeron; Paterson, Craig; Fryer, Simon; Diana, Jake; Blackwell, Jade; Meyer, Michelle L.; Stoner, Lee (Frontiers in Cardiovascular Medicine, 2023)
OBJECTIVE Pulse-wave velocity (PWV), a common measure of arterial stiffness, can be measured continuously and across multiple body sites using photoplethysmography (PPG). The objective was to determine whether a simple photoplethysmography PPG PWV method agrees with a referent device. APPROACH PPG heart-finger PWV (hfPWV) and heart-toe PWV (htPWV) were compared to oscillometric carotid-wrist PWV (cwPWV) and carotid-ankle PWV (caPWV) referent measurements, respectively. In 30 adults (24.6 ± 4.8 y, body mass index 25.2 ± 5.9 kg/m2, 18 female), three measurements were made: two supine baseline measurements (Base 1, Base 2) and one measurement (Tilt) 5 minutes after a modified head-up tilt test (mHUTT). Overall agreement and repeated measures agreement (change in PPG PWV from Base to Tilt versus change in referent PWV from Base to Tilt) were calculated using linear mixed models. Agreement estimates were expressed as intra-class correlation coefficients (ICC). MAIN RESULTS For hfPWV there was strong overall agreement (ICC: 0.77, 95%CI: 0.67 – 0.85), but negligible and non-significant repeated measures agreement (ICC: 0.10, 95%CI: -0.18 – 0.36). For htPWV, there was moderate overall agreement (ICC:0.50, 95%CI: 0.31 – 0.65) and strong repeated measures agreement (ICC: 0.81, 95%CI: 0.69 – 0.89). SIGNIFICANCE PPG can continuously measure PWV at multiple arterial segments with moderate-strong overall agreement. While further work with upper-limb PPG PWV is needed, PPG can adequately capture acute changes in lower-limb PWV.